Physicochemical Analysis and Molecular Modeling of the Fosinopril β-Cyclodextrin Inclusion Complex - Udrescu, Lucreția; Sbârcea, Laura; Fuliaș, Adriana; Ledeți, Ionuț; Vlase, Gabriela; Barvinschi, Paul; Kurunczi, Ludovic (Journal of Spectroscopy, 2014)
This research investigates the interaction between fosinopril sodium (FOS) and beta-cyclodextrin (β-CD) in aqueous solution and in solid state, in order to prove the formation of an inclusion complex between the two components. The stoichiometry of the inclusion complex was found as 1 : 1 by employing continuous variation method in UV. The formation constant was calculated as 278.93 M−1 using Benesi-Hildebrand equation. The kneaded product (KP) and the physical mixture (PM) were further experimentally examined, using FTIR, powder X-ray diffractometry, and thermal analysis. The results confirm that the physicochemical properties of the FOS/β-CD KP are different from FOS and that the kneading method leads to formation of solid state inclusion complex between FOS and β-CD. Structural studies of the FOS/β-CD were carried out using molecular modeling techniques, in order to explain the complexation mechanism and the host-guest geometry.